2021
DOI: 10.3389/fimmu.2021.668974
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Neutrophil Extracellular Traps in Disease Activity Associated With IgA Vasculitis

Abstract: ObjectivesThis aim of this study was to determine whether neutrophil extracellular traps (NETs) are involved in the pathogenesis of IgA vasculitis (IgAV) and investigate whether the circulating NETs levels are associated with disease activity in children.MethodsWe performed a case-control study and collected blood samples from 193 children with different stages of IgAV (61 were at the onset stage, 64 at the remission stage, 43 at the active stage, and 25 were undergoing drug withdrawal). A total of 192 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…The ECG loading rate was determined from the ratio of the initial DNA content of the constructs and that 24 h after combination with ECG. The DNA content of the samples ( n = 5 per group) was quantified using a Quant-iT PicoGreen dsDNA assay (Invitrogen, Carlsbad, CA, United States) as previously described ( Chen et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The ECG loading rate was determined from the ratio of the initial DNA content of the constructs and that 24 h after combination with ECG. The DNA content of the samples ( n = 5 per group) was quantified using a Quant-iT PicoGreen dsDNA assay (Invitrogen, Carlsbad, CA, United States) as previously described ( Chen et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Aleyd et al ( 56 ) demonstrated that IgA enhances NETosis as an effective defense mechanism to eliminate pathogens at mucosal surfaces. In contrast, neutrophil activation by IgA immune complex is also known to contribute to the immunopathogenesis of autoimmune diseases, such as IgA vasculitis, and nephropathy ( 5759 ). In respiratory viral disease models, such as influenza and SARS-CoV-2, the formation of an IgA-virus immune complex led to exacerbated NETosis of neutrophils isolated from peripheral blood mononuclear cells (PBMCs) ex vivo ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study ( 13 ) revealed that serum degradation of NETs significantly declines in children with IgAV onset and active IgAV. Children in drug withdrawal had a normal level of NETs degradation.…”
Section: Mechanism Of Nets In Igavmentioning
confidence: 95%
“…The study evaluated components of NETs, which included cell-free DNA (cf-DNA), myeloperoxidase-DNA (MPO-DNA), citrullinated-histone H3 (cit-H3), neutrophil elastase (NE), and cathelicidin antimicrobial peptides (CAMP, LL37). The level of NETs significantly increased in children with IgAV onset and active stage, while the level of NETs gradually returned to normal in children in the remission stage and drug withdrawal ( 13 ). In autoimmune diseases, excessive NETs are known to act as an exposed autoantigen in vivo , inducing the production of autoantibodies, thereby increasing the intensity of the inflammatory response.…”
Section: Nets Involved In the Pathogenesis Of Igavmentioning
confidence: 99%
See 1 more Smart Citation